3x-9+4x=-12

Simple and best practice solution for 3x-9+4x=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-9+4x=-12 equation:


Simplifying
3x + -9 + 4x = -12

Reorder the terms:
-9 + 3x + 4x = -12

Combine like terms: 3x + 4x = 7x
-9 + 7x = -12

Solving
-9 + 7x = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 7x = -12 + 9

Combine like terms: -9 + 9 = 0
0 + 7x = -12 + 9
7x = -12 + 9

Combine like terms: -12 + 9 = -3
7x = -3

Divide each side by '7'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| log(x-1)25x=2 | | 3x+(x+20)+3x=180 | | 102=1/2(10+7) | | 9y-2=6y+1 | | 15.9n=413.4 | | 4/3(x-17)=36 | | -(-9)+2y+(-9)+6= | | 7w-3(4w+8)=7 | | X^2-6Y+2x+y^2=9 | | 23=2b+5b | | x+2x(5)+2x(2x)(10)+2x(2x)-3(25)+2x(100)+2x(500)=9382 | | 21x=6+17x-26 | | 2m^2-5m-2=0 | | 3j-1+6=0 | | 4m-3m=2 | | g(x)=36 | | 8-2x-3x=-16-8x | | 2(x+2)=5x-3 | | -6(3z-7)=33 | | 36-(3x+4)=2(x+4)+x | | x-5x+4x-7x= | | x^3-5x^2+2x=-1 | | 3+2k=17 | | x=7ln(y^2-48) | | 2w^2+7w=0 | | 7x=19(2x-7) | | -2x-x+1=0 | | 0.2x^5-2x^3+1.8x+5=0 | | 7+12p=-5 | | -2x-6=2-4-(x-1) | | 0.2x^5-2x^3+1.8x+2=0 | | R^2+10r-30=0 |

Equations solver categories